Staircase / Muhammad Faisal Azizam - Azizam, Muhammad Faisal (Universiti Teknologi MARA, Perak, 2022)
Staircase is a one of the basic components that connect different floors in building structure. Therefore, this report will explain the detail of method construction of staircase and the problem with their solution. This report is carried out at DTC W407 site Pavillion Damansara Town Centre, Damansara Kuala Lumpur. The objective of the report is to gain knowledge and information on staircase construction method and identify the issue on staircase and the way to overcome the issue. It will focus on staircase construction flow to determine the method that are use and the problems that are faced. To illustrate the method of constructing a staircase from setting out to the finishing work that must be follow the sequence of work as per approved in method statement. It also investigates the problem that might occur in construction of staircase with the effective solution to eliminate the problem without cause any trouble that prevent future work.